Development of highly photosensitive low loss inorganic sol-gel films for direct ultraviolet-imprinting of planar waveguides - Rajni (2008)
Highly photosensitive sol-gel derived inorganic 0.2GeO2:0.8SiO2 (germanosilicate) films have been developed to simplify the fabrication of photonic devices using a single step direct UV-imprinting (DUI) technique. The KrF excimer laser (248 nm) light induced refractive index change (?n) of germanosilicate films has been investigated. The values of ?n increases with UV-illumination time, and saturated at ~ 0.0094 in case of densified thin films (~ 200 nm), and at ~ 0.005 in case of thick films (~ 3 µm). This high value of ?n is attributed to the creation of oxygen deficiency, and found to be high enough to form optical guiding channel. Photonic waveguide devices such as channel-waveguides, optical splitters and switches have been successfully fabricated using the DUI technique and the results are found to be in good agreement with the theoretical results.